Mechanical engineering systems - Gentle, Richard
The authors of Mechanical Engineering Systems have taken a highly practical approach within this book, bringing the subject to life through a lively text supported by numerous activities and case studies. Little prior knowledge of mathematics is assumed and so key numerical and statistical techniques are introduced through unique Maths in Action features. The IIE Textbook Series from Butterworth-Heinemann*Student-focused textbooks with numerous examples, activities, problems and knowledge-check questions*Designed for a wide range of undergraduate courses*Real-world engineering examples at the h.